2022
DOI: 10.1063/5.0120723
|View full text |Cite
|
Sign up to set email alerts
|

High In content nitride sub-micrometer platelet arrays for long wavelength optical applications

Abstract: We demonstrate high, up to 30% In content InGaN sub-micrometer platelets on GaN by metalorganic vapor phase epitaxy. These InGaN platelets were selectively grown on flat GaN seeds formed in sub-micrometer-scale openings in a SiNx mask. The platelets were highly uniform without any dislocations or pits, with an atomically flat (0001) surface. The typical height was ∼120 nm, which significantly exceeded the normal critical layer thickness of a c-plane InGaN film. The strain state was comprehensively characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Cai et al reported high‐quality and uniform InGaN platelet arrays by selectively depositing InGaN onto submicrometer scale GaN seed arrays by MOVPE. [ 44 ] Such platelets showed a height of 120 nm, where the indium content increased from 15% at the InGaN/GaN interface to about 30% at the atomically flat surface. The obtained high‐quality InGaN pseudosubstrate can serve as high‐quality strain‐relaxed templates for high efficiency, long wavelength optical applications.…”
Section: Template For Long‐wavelength Led Growthmentioning
confidence: 99%
“…Cai et al reported high‐quality and uniform InGaN platelet arrays by selectively depositing InGaN onto submicrometer scale GaN seed arrays by MOVPE. [ 44 ] Such platelets showed a height of 120 nm, where the indium content increased from 15% at the InGaN/GaN interface to about 30% at the atomically flat surface. The obtained high‐quality InGaN pseudosubstrate can serve as high‐quality strain‐relaxed templates for high efficiency, long wavelength optical applications.…”
Section: Template For Long‐wavelength Led Growthmentioning
confidence: 99%
“…30) We have recently reported on a method to directly fabricate an InGaN platelets array by introducing a flat GaN seed layer before selectively growing InGaN. 31) The use of a low-dislocation-density GaN substrate ensures a homogeneous InGaN platelet array with a flat surface compared with other methods previously reported. 24,25) These InGaN platelets have a high In content of up to 30% and were proved to be dislocation-and pit-free while much strain is relaxed elastically owing to their small size.…”
mentioning
confidence: 99%
“…The details of mask patterning before growth and the growth conditions of the GaN seed layer and InGaN platelets have been reported elsewhere. 31) The InGaN platelets were grown at 810 °C, 795 °C and 780 °C to obtain samples with different base In contents, referred to as series 2-4, respectively. For comparison, platelets were also grown without feeding trimethylindium (TMI), which led to pure GaN platelets, referred to as series 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations